2011
DOI: 10.1007/s11069-011-9894-5
|View full text |Cite|
|
Sign up to set email alerts
|

Design and quantification of an extreme winter storm scenario for emergency preparedness and planning exercises in California

Abstract: The USGS Multihazards Project is working with numerous agencies to evaluate and plan for hazards and damages that could be caused by extreme winter storms impacting California. Atmospheric and hydrological aspects of a hypothetical storm scenario have been quantified as a basis for estimation of human, infrastructure, economic, and environmental impacts for emergency-preparedness and flood-planning exercises. In order to ensure scientific defensibility and necessary levels of detail in the scenario description… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…We would not suggest that the quantitative flood discharges computed using VIC be used for structural designs or details of flood management. From these analyses, we conclude (as others have, for example Dettinger et al 2004;Miller et al 2003;Anderson et al 2006;Dettinger et al 2009;Raff et al 2009) that flood regimes in Californian Sierra Nevada are vulnerable to change with future climate change. With the models used here, flood magnitudes and frequencies tend overall (but not universally) to increase, even under scenarios with significant drying.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We would not suggest that the quantitative flood discharges computed using VIC be used for structural designs or details of flood management. From these analyses, we conclude (as others have, for example Dettinger et al 2004;Miller et al 2003;Anderson et al 2006;Dettinger et al 2009;Raff et al 2009) that flood regimes in Californian Sierra Nevada are vulnerable to change with future climate change. With the models used here, flood magnitudes and frequencies tend overall (but not universally) to increase, even under scenarios with significant drying.…”
Section: Discussionsupporting
confidence: 66%
“…VIC has been used extensively in a variety of water resources applications from studies of climate variability, hydrologic forecasting and climate change studies (for example, Nijssen et al 2001;Maurer et al 2002;Sheffield and Wood 2007;Wood and Lettenmaier 2006;Dettinger et al 2011;Cayan et al 2010). Mote et al (2005) found reasonable agreement between the spatial pattern of observed SWE and the VIC simulated values.…”
Section: Hydrological Modelmentioning
confidence: 89%
See 1 more Smart Citation
“…(1) in section 2c] combines with near-neutral moist static stability (Ralph et al 2005;Neiman et al 2008a) and strong orographic forcing (e.g., Smith et al 2010) to produce large amounts of precipitation (Neiman et al 2008b;Dettinger et al 2004). Consequently, AR storms have been linked with flooding and are a critical component of the water budget of the western United States (Ralph et al 2006;Dettinger et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The common underlying hydrometeorological factor that contributed to the 1996-1997 flooding episode was the presence of "atmospheric rivers" (ARs), which accounted for advective transport of water vapor along highly concentrated streamlines (Dettinger et al, 2012). The ARs that extended over much of California and the Pacific Northwest, when assisted with a strong low-level wind, carried a large amount of moisture from the Pacific Ocean that eventually precipitated inland.…”
Section: Study Regionsmentioning
confidence: 99%